Are rural children of work-away parents really left behind? Voices from rural teachers. (October 2020) - Fu, Linyun; Zhu, Yiqi
Highlights: Many children of work-away parents are successful in school settings. Adequate supports and effective methods are key for the positive development. Suitable training programs should be provided to improve teachers' skills. Risk factors for children in rural China are oversimplified under the stereotypes of "left-behind children." Comprehensive risk assessments need to be conducted for all rural children. Abstract: This study adopted the Positive Youth Development Approach and used semi-structured interviews with fifty rural teachers to discover environmental factors that foster the success of children of work-away parents (often called left-behind children in many studies) and to understand current challenges from rural teachers' perspectives. The results of this study indicated children of work-away parents can be successful in school settings when parents or teachers have a strong belief in the success of children and effective methods in place to ensure the quality of learning. In addition, teachers can better support their students if they can be relieved from excessive administrative burdens and gain practical methods to work with students with special needs. Furthermore, we found that the real risk factors for children in rural China are oversimplified under the stereotypes of "left-behind children." This study calls for a comprehensive risk assessment for all rural children, considering the complexity of the status and potential stigmatization towards them and specific training and support for work-away parents, direct caregivers, and teachers to form an alliance to reduce the risk factors and enhance the well-being of rural children.